Case report: the effects of cerebellar tDCS in bilingual post-stroke aphasia - Coemans, Silke; Struys, Esli; Tsapkini, Kyrana; Paquier, Philippe; Vandenborre, Dorien; Keulen, Stefanie (Frontiers in Human Neuroscience, 2023)
Transcranial Direct Current Stimulation may be a useful neuromodulation tool for enhancing the effects of speech and language therapy in people with aphasia, but research so far has focused on monolinguals. We present the effects of 9 sessions of anodal cerebellar tDCS (ctDCS) coupled with language therapy in a bilingual patient with chronic post-stroke aphasia caused by left frontal ischemia, in a double-blind, sham-controlled within-subject design. Language therapy was provided in his second language (L2). Both sham and anodal treatment improved trained picture naming in the treated language (L2), while anodal ctDCS in addition improved picture naming of untrained items in L2 and his first language, L1. Picture description improved in L2 and L1 after anodal ctDCS, but not after sham.